Pipelines for water conveyance and drainage - Beieler, Roger W. (American Society of Civil Engineers, 2013)
Prepared by the Task Committee on Pipelines for Water Conveyance and Drainage of the Irrigation Delivery and Drainage Systems Committee of the Irrigation and Drainage Council of the Environmental and Water Resources Institute of the American Society of Civil Engineers Pipelines for Water Conveyance and Drainage offers a concise listing and description of 11 types of pipe commonly used for water conveyance and drainage. For each type of pipe, 20 characteristics are described, including such physical attributes as material, available sizes, standard lengths, protective linings and coatings, joints, and fittings. Performance characteristics include allowable internal pressure, external load capabilities, hydraulic resistance factor, wave speed, allowable leakage rates, and water quality tolerances. Installation and maintenance criteria include specifications; tapping methods; repair methods; installation, backfill, and protective requirements; and useful life. Information about common standards, industry groups, and reference publications is also included. This Manual of Practice (MOP) pertains to the following types of pipe: concrete, welded steel, ductile iron, polyvinyl chloride (PVC), high-density polyethylene (HDPE) pressure, polyethylene profile wall, PVC and polypropylene profile wall, corrugated polyethylene, fiberglass, corrugated metal, and vitrified clay pipe and clay drain tile. Design engineers, utility managers, planners, and educators will find MOP 125 to be an essential reference for designing, installing, and maintaining pipelines that convey water and drainage. Design engineers, utility managers, planners, and educators will find MOP 125 to be an essential reference for designing, installing, and maintaining pipelines that convey water and drainage.
Keywords: Water-pipes -- Design and construction.; Pipelines -- Design and construction.; elektronické knihy; electronic books